Telegram from Fridel G. Halstead to the Homburgers - Halstead, Fridel G.
Fridel G. Halstead asks Marianne (1903-1986) and Viktor Homburger (1888-1968) if they have received affidavits.
Keywords: Homburger, Viktor, 1888-1968; Homburger, Marianne, 1903-1986; Halstead, Fridel G.; Bredig, Georg, 1868-1944; Affidavits